Prevalence and "Red Flags" Regarding Specified Causes of Back Pain in Older Adults Presenting in General Practice. Issue 3 (1st March 2016) - Enthoven, Wendy T.M.; Geuze, Judith; Scheele, Jantine; Bierma-Zeinstra, Sita M.A.; Bueving, Herman J.; Bohnen, Arthur M.; Peul, Wilco C.; van Tulder, Maurits W.; Berger, Marjolein Y.; Koes, Bart W.; Luijsterburg, Pim A.J.
Abstract : Background: In a small proportion of patients experiencing unspecified back pain, a specified underlying pathology is present. Objective: The purposes of this study were: (1) to identify the prevalence of physician-specified causes of back pain and (2) to assess associations between "red flags" and vertebral fractures, as diagnosed by the patients' general practitioner (GP), in older adults with back pain. Methods: The Back Complaints in the Elders (BACE) study is a prospective cohort study. Patients (aged >55 years) with back pain were included when consulting their GP. A questionnaire was administered and a physical examination and heel bone densitometry were performed, and the results determined back pain and patient characteristics, including red flags. Participants received a radiograph, and reports were sent to their GP. The final diagnoses established at 1 year were collected from the GP's patient registry. Results: Of the 669 participants included, 6% were diagnosed with a serious underlying pathology during the 1-year follow-up. Most of these participants (n=33, 5%) were diagnosed with a vertebral fracture. Multivariable regression analysis showed that age of ≥75 years, trauma, osteoporosis, a back pain intensity score of ≥7, and thoracic pain were associated with a higher chance of getting the diagnosis of a vertebral fracture. Of these variables, trauma showed the highest positive predictive value for vertebral fracture of 0.25 (95% confidence interval=0.09, 0.41) and a positive likelihood ratio of 6.2 (95% confidence interval=2.8, 13.5). A diagnostic prediction model including the 5 red flags did not increase these values. Limitations: Low prevalence of vertebral fractures could have led to findings by chance. Conclusions: In these older adults with back pain presenting in general practice, 6% were diagnosed with serious pathology, mainly a vertebral fracture (5%). Four red flags were associated with the presence of vertebral fracture.